2005
DOI: 10.1111/j.1540-8167.2005.40788.x
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Higher Heart Rate Variability Is Not Better Heart Rate Variability: Results of Graphical and Nonlinear Analyses

Abstract: Abnormal HR patterns that elevate many HRV indices are prevalent among the elderly and associated with higher risk of mortality. Consideration of abnormal HRV may improve HRV-based risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
158
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(168 citation statements)
references
References 22 publications
8
158
0
2
Order By: Relevance
“…4 This means that the heart rate-to-HRV correlation is affected by SND, 2 and a higher HRV is not always a better HRV, which is sometimes associated with a higher risk of mortality. 25 Thus, the present results also indicate that abnormally higher HRV, compared with age-matched reference values, might suggest the presence of SND.…”
Section: Discussionsupporting
confidence: 62%
“…4 This means that the heart rate-to-HRV correlation is affected by SND, 2 and a higher HRV is not always a better HRV, which is sometimes associated with a higher risk of mortality. 25 Thus, the present results also indicate that abnormally higher HRV, compared with age-matched reference values, might suggest the presence of SND.…”
Section: Discussionsupporting
confidence: 62%
“…These studies analyzed the shape of the Poincare plots and related it to pathology. For example, in healthy subjects the Poincare plot was found to be fan-shaped as a result of an increasing beat-to-beat R-R dispersion with increasing R-R interval duration (10,23), while in pathological subjects the shape is more complex (21). Quantitative analysis of the Poincare plots is based on indexes that are essentially correlated with the area occupied by the cloud of points in the plane (R-R(i),R-R(iϩ)) (10,23).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several groups have dealt with the scatterplot in the plane (R-R(i),R-R(iϩ)) more commonly referred to as two-dimensional return map or Poincare plot [see e.g., 10,21,23]. These studies analyzed the shape of the Poincare plots and related it to pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found that many older subjects and patients with cardiovascular disease have an increased beat-to-beat variability that is irregular and does not reflect underlying respiratory sinus arrhythmia (1). We have called this erratic rhythm.…”
mentioning
confidence: 99%